Steric Engineering Enables Efficient and Photostable Wide‐Bandgap Perovskites for All‐Perovskite Tandem Solar Cells. Issue 26 (23rd May 2022) - Wen, Jin; Zhao, Yicheng; Liu, Zhou; Gao, Han; Lin, Renxing; Wan, Sushu; Ji, Chenglong; Xiao, Ke; Gao, Yuan; Tian, Yuxi; Xie, Jin; Brabec, Christoph J.; et al.
Abstract: Wide‐bandgap (WBG, ≈1.8 eV) perovskite is a crucial component to pair with narrow‐bandgap perovskite in low‐cost monolithic all‐perovskite tandem solar cells. However, the stability and efficiency of WBG perovskite solar cells (PSCs) are constrained by the light‐induced halide segregation and by the large photovoltage deficit. Here, a steric engineering to obtain high‐quality and photostable WBG perovskites (≈1.8 eV) suitable for all‐perovskite tandems is reported. By alloying dimethylammonium and chloride into the mixed‐cation mixed‐halide perovskites, wide bandgaps are obtained with much lower bromide contents while the lattice strain and trap densities are simultaneously minimized. The WBG PSCs exhibit considerably improved performance and photostability, retaining >90% of their initial efficiencies after 1000 h of operation at maximum power point. With the triple‐cation/triple‐halide WBG perovskites enabled by steric engineering, a stabilized power conversion efficiency of 26.0% in all‐perovskite tandem solar cells is further obtained. The strategy provides an avenue to fabricate efficient and stable WBG subcells for multijunction photovoltaic devices. Abstract : Efficient and photostable wide‐bandgap (WBG) perovskites (≈1.8 eV) with only 25 mol% bromide are enabled by steric engineering via alloying dimethylammonium and chloride. The WBG single‐junction cells, with a high efficiency of 17.7%, exhibit promising operational stability under 1‐sun illumination ( T 90 of 1045 h). This strategy enables all‐perovskite tandem with an impressive stabilized efficiency of 26.0%.